2014
DOI: 10.1039/c3nr04853e
|View full text |Cite
|
Sign up to set email alerts
|

The chiral magnetic nanomotors

Abstract: Propulsion of the chiral magnetic nanomotors powered by a rotating magnetic field is in the focus of the modern biomedical applications. This technology relies on strong interaction of dynamic and magnetic degrees of freedom of the system. Here we study in detail various experimentally observed regimes of the helical nanomotor orientation and propulsion depending on the actuation frequency, and establish the relation of these two properties with the remanent magnetization and geometry of the helical nanomotors… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
132
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(142 citation statements)
references
References 21 publications
(74 reference statements)
10
132
0
Order By: Relevance
“…They showed that microswimmers with such magnetization had much reduced wobbling compared to microswimmers with random easy axis, as well as improved swimming characteristics. In addition, in a theoretical examination of the rotational and swimming behavior of helices with permanent magnetic dipole, Morozov and Leshansky [42] concluded that for such microswimmers, it is optimal to have the magnetic dipole perpendicular to the helical axis to minimize wobbling.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They showed that microswimmers with such magnetization had much reduced wobbling compared to microswimmers with random easy axis, as well as improved swimming characteristics. In addition, in a theoretical examination of the rotational and swimming behavior of helices with permanent magnetic dipole, Morozov and Leshansky [42] concluded that for such microswimmers, it is optimal to have the magnetic dipole perpendicular to the helical axis to minimize wobbling.…”
Section: Introductionmentioning
confidence: 99%
“…Man and Lauga [40] showed that during wobbling the precession angle scales as inverse frequency using nu merics and asymptotics of nearly straight helices. Ghosh e t a l. [39,41] and Morozov and Leshansky [42] investi gated the transition of stability from tumbling to wobbling behavior as frequency increases by treating the rotational dynamics as that of ellipsoids numerically and analytically, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11] dealt with isolated asymmetric objects in Stokes flow, which exhibit a chiral response. The object's chiral response is encoded in the offdiagonal block of its self-mobility matrix, referred to as the twist matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Such richer responses can be exploited to obtain "steerable colloids" -objects whose orientation and transport can be controlled in much more detail. For example, applying a torque by a rotating uniform magnetic field was used to achieve efficient transport of chiral magnetic objects 8 . Another example, which is the main issue of the present work, is the ability to achieve orientational alignment of asymmetric objects by applying an external force [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%